Clinical Applications and Future Directions of Minimal Residual Disease Testing in Multiple Myeloma - Oliva, Stefania; D'Agostino, Mattia; Boccadoro, Mario; Larocca, Alessandra (Frontiers in Oncology, 2020)
In the last years, the life expectancy of multiple myeloma (MM) patients has substantially improved thanks to the availability of many new drugs. Our ability to induce deep responses has improved as well, and the treatment goal in patients tolerating treatment moved from the delay of progression to the induction of the deepest possible response. As a result of these advances, a great scientific effort has been made to redefine response monitoring, resulting in the development and validation of high-sensitivity techniques to detect minimal residual disease (MRD). In 2016, the International Myeloma Working Group (IMWG) updated MM response categories defining MRD-negative responses both in the bone marrow (assessed by next-generation flow cytometry or next-generation sequencing) and outside the bone marrow. MRD is an important factor independently predicting prognosis during MM treatment. Moreover, using novel combination therapies, MRD-negative status can be achieved in a fairly high percentage of patients. However, many questions regarding the clinical use of MRD status remain unanswered. MRD monitoring can guide treatment intensity, although well-designed clinical trials are needed to demonstrate this potential. This mini-review will focus on currently available techniques and data on MRD testing and their potential future applications.